PAKISTAN SOCIETY OF HEPATOLOGY (PSH) POSITION STATEMENT: RENAMING NON-ALCOHOLIC FATTY LIVER DISEASE (NAFLD) TO STEATOTIC LIVER DISEASE (SLD), ENDORSEMENT OF NEW MULTI-SOCIETY NOMENCLATURE - Ali, Zeeshan; Mariam Riaz,; Altaf Alam,; Javed Iqbal Faroqi, (Journal of Ayub Medical College Abbottabad, 2023)
The Nomenclature of diseases intends to have a system whereby diagnosis can be suitably catalogued without ambiguity or confusion. Therefore, the nomenclature of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH), is ambiguous owing to perplexity in terms of aetiology and possible stigmatizing language. To address these concerns, there is an apparent need for change in the current nomenclature.